2023
DOI: 10.1039/d2qm01147f
|View full text |Cite
|
Sign up to set email alerts
|

The nonhalides in perovskite solar cells

Abstract: Recently, the halide perovskites solar cells (PSCs) have accomplished the most remarkable progress in the emerging photovoltaic technology. However, their poor stability hinders the way of commercialization. Notably, the high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…The search for new A-site cation spacers and the combination of A-and X-site such as GA + and SCN − which contribute to form a 2D/3D vertical heterojunction in TPSCs and PEA + and SCN − which were used to form 2D/quasi-2D/3D tin perovskite structure may be the two promising directions for preparing more stable TPSCs in the future. [135,138,139,164,165] 3) The unique preparation process and device structure of TP-SCs are both important for the performance and stability of TPSCs. Hayase and co-workers and Ning and co-workers tailored exclusive preparation methods and device structures for TPSCs based on the characteristics of tin perovskite and obtained 14.7% and 14.09% PCE, respectively.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…The search for new A-site cation spacers and the combination of A-and X-site such as GA + and SCN − which contribute to form a 2D/3D vertical heterojunction in TPSCs and PEA + and SCN − which were used to form 2D/quasi-2D/3D tin perovskite structure may be the two promising directions for preparing more stable TPSCs in the future. [135,138,139,164,165] 3) The unique preparation process and device structure of TP-SCs are both important for the performance and stability of TPSCs. Hayase and co-workers and Ning and co-workers tailored exclusive preparation methods and device structures for TPSCs based on the characteristics of tin perovskite and obtained 14.7% and 14.09% PCE, respectively.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…Previous reports have confirmed that employing a low concentration (below 1 mg/mL) of PEAI/chlorobenzene as the antisolvent washing to fabricate perovskite films, the PEA + cations were located exclusively at the surface of the perovskite film, thus achieving the passivation on the surface defects at the perovskite/ETL interface. Hence, we believed that the p-FPEAI additive is located merely at the top surface; after the washing, their passivation function was already achieved by coordinating the perovskite defects with the great electron affinity of F – anions and PEA + cations. …”
Section: Resultsmentioning
confidence: 99%
“…In light of the global energy crisis and the increasing issue of environmental pollution, renewable and clean energy are essential for sustainable development. [1][2][3][4][5] The ability of solar cells to convert sunlight directly into electricity makes them one of the most popular renewable energy technologies today. [6][7][8][9][10] Among many solar cells, silicon solar cells occupy the primary photovoltaic market due to their mature technology, non-toxicity, long life, low cost, etc.…”
Section: Introductionmentioning
confidence: 99%